Des semis et des clones - Malou Delplancke; Yildiz Aumeeruddy-Thomas (Revue d'ethnoécologie)
For the rural Bni Boufrah society, in the Moroccan Rif, almonds (l’luz) play a pivotal role in a semi-arid low mountain agro-sylvo-pastoral system combining cereals, pulses, almonds and animal husbandry. Almond fruit, quite commonly used as currency, is a bankable standing crop; in this respect, there is a distinction between hard shell almonds (l’luz beldi), which are stored throughout the year, and soft shell almonds (l’luz snan or l’luz romi), which cannot be preserved as long. Almonds are traded for services, tendered like money at the souk, as and when needed by households, or will even be donated. Whether it is by natural regeneration in forests, controlled sowing in fields or vegetative propagation by grafting (telqem) in gardens, almonds are characterized by a management of their seeds (diversification by sexual reproduction) and clones (identical reproduction by vegetative propagation) in a spatial and temporal framework within territories. As prototypical trees of the Eastern Rif, almond stands have “integrated” over time successive inputs by almonds brought from elsewhere, by knowledge and techniques that create a tension between here —locally referred to as beldi and elsewhere called romi thus reflecting human identities in this territory. As far as gathering, agriculture and horticulture are concerned, practices overlap in socially differentiated spaces. This is why the status of the almond varies from that of a tolerated, to a fostered and even a highly domesticated tree, which prompts us to think about the domestication of a species in its imbricated spatial and temporal framework, concretely expressed in territories and agricultural landscapes. Rooted in time and space, an almond tree is a link between generations, between the living and the forebears, tradition and modernity, but also between what originates from here (beldi) and what comes from elsewhere (romi). Almonds tell us how people can reconcile time and space in order to think of history and territory simultaneously. By the combination of sexual and vegetative propagation, men stake their territories with almond trees and their own lives while integrating elements coming from the borders. As pivotal as men, almond trees thus form part of a hybrid community consisting of humans and non-humans.